Penerapan Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat Terhadap Pelaku Minum Khamr Perspektif Hukum Pidana Islam - Yunada Putri Rahmawati; Ali Khosim; Deden Najmudin (Maqasid: Jurnal Studi Hukum Islam, 2025)
Alcoholic beverages are considered as one form of sin in Islam that has the potential to damage individual morals and the social order of society. The circulation of alcoholic beverages is an important issue, especially in areas that implement Islamic law, such as Aceh. Aceh is the only region in Indonesia that formally implements Islamic law, which is reflected in Aceh Qanun Number 6 of 2014 concerning Jinayat Law. This study aims to analyze and evaluate the implementation of Aceh Qanun Number 6 of 2014 concerning Jinayat Law against perpetrators of drinking alcohol from the perspective of Islamic criminal law. This study uses a normative research method, using a normative juridical approach, namely research that focuses on the analysis and interpretation of legal norms using qualitative data types and library research data collection techniques. The results of this study are that Aceh Qanun Number 6 of 2014 punishes perpetrators of drinking alcohol with caning as a deterrent. The effectiveness of this qanun can be seen from the changes in the perpetrators' behavior, although ongoing evaluation and guidance are still needed so that the objectives of the law are achieved in a complete, balanced, and humane manner. Keywords: Alcoholic drinks, Aceh Qanun Number 6 of 2014, Caning punishment